Respuesta :
(a) Recall that
[tex]\dfrac{\mathrm d[\sin^{-1}x]}{\mathrm dx}=\dfrac1{\sqrt{1-x^2}}[/tex]
[tex]\dfrac{\mathrm d[\ln x]}{\mathrm dx}=\dfrac1x[/tex]
[tex]\dfrac{\mathrm d[\sqrt x]}{\mathrm dx}=\dfrac1{2\sqrt x}[/tex]
Then by the chain rule,
[tex]y=\sin^{-1}(\sqrt x)+\ln(\sqrt x)[/tex]
[tex]\implies\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\mathrm d[\sin^{-1}(\sqrt x)+\ln(\sqrt x)]}{\mathrm dx}[/tex]
[tex]=\dfrac1{\sqrt{1-(\sqrt x)^2}}\dfrac{\mathrm d[\sqrt x]}{\mathrm dx}+\dfrac1{\sqrt x}\dfrac{\mathrm d[\sqrt x]}{\mathrm dx}[/tex]
[tex]=\dfrac1{2\sqrt x\sqrt{1-x}}+\dfrac1{2(\sqrt x)^2}[/tex]
[tex]=\dfrac1{2\sqrt{x-x^2}}+\dfrac1{2x}[/tex]
[tex]=\boxed{\dfrac{x+\sqrt{x-x^2}}{2x\sqrt{x-x^2}}}[/tex]
(b) I'll assume [tex]\log x[/tex] refers to the logarithm of base [tex]e[/tex]. Recall that
[tex]\dfrac{\mathrm d[e^x]}{\mathrm dx}=e^x[/tex]
[tex]2^x=e^{\log2\,x}\implies\dfrac{\mathrm d[2^x]}{\mathrm dx}=e^{\log2\,x}\dfrac{\mathrm d[\log2\,x]}{\mathrm dx}=\log2\cdot2^x[/tex]
Then using the chain rule and implicit differentiation, we get
[tex]e^y=2^x\log x-e^{2x}[/tex]
[tex]\implies e^y\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\mathrm d[2^x]}{\mathrm dx}\log x+2^x\dfrac{\mathrm d[\log x]}{\mathrm dx}-e^{2x}\dfrac{\mathrm d[2x]}{\mathrm dx}[/tex]
[tex]e^y\dfrac{\mathrm dy}{\mathrm dx}=\log2\cdot2^x\log x+\dfrac{2^x}x-2e^{2x}[/tex]
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\log2\cdot2^x\log x+\frac{2^x}x-2e^{2x}}{e^y}[/tex]
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\dfrac{\log2\cdot2^x\log x+\frac{2^x}x-2e^{2x}}{2^x\log x-e^{2x}}[/tex]
[tex]\dfrac{\mathrm dy}{\mathrm dx}=\boxed{\dfrac{\log2\cdot2^xx\log x+2^x-2xe^{2x}}{x(2^x\log x-e^{2x})}}[/tex]
If instead [tex]\log x=\log_{10}x[/tex] denotes the base 10 logarithm, you need only make the following adjustment:
[tex]\log x=\dfrac{\ln x}{\ln 10}\implies\dfrac{\mathrm d[\log_{10}x]}{\mathrm dx}=\dfrac1{\ln10\,x}[/tex]
where [tex]\ln x[/tex] is logarithm of base [tex]e[/tex].